Nepal : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2019)
This Selected Issues paper examines the degree to which inflation co-moves between India and a panel of countries in Asia. The paper shows that the considerable co-movement in headline inflation rates between India and Nepal is driven almost exclusively by food-inflation co-movement. By contrast, the role for inflation spillovers emanating from India in driving non-food inflation in Nepal appears limited. The implication is that Nepal should rely on domestic monetary policy rather than stable inflation in India to achieve stable domestic inflation. The main takeaway from the results is that food inflation co-movement between India and other countries is higher in cases where the co-movement in rainfall deviations from seasonal norms is highest. Since core inflation co-movement is weak, idiosyncratic domestic factors such as economic slack, exchange-rate movements, and differing degrees of passthrough from food- and energy-price shocks play an important role. This finding is critically important for monetary policy, especially since domestic policy is primarily effective only in controlling core inflation. Thus, domestic monetary policy needs to be calibrated to domestic inflationary pressures-Nepal cannot necessarily rely on stable inflation in India to achieve stable domestic inflation.